Unveiling Key Drivers to Enhance Global Customer Satisfaction: Mengungkap Faktor Pendorong Utama untuk Meningkatkan Kepuasan Pelanggan Global - Jamilah, Hafshah; Supardi, Supardi; Indayani, Lilik (Indonesian Journal of Innovation Studies, 2024)
This quantitative study investigates the influence of service quality, price, and brand image on customer satisfaction at PT. Pos Indonesia Sultan Agung Magersari Sidoarjo. Using a sample of 85 respondents and multiple linear regression analysis, the research finds significant positive effects of service quality, price, and brand image on customer satisfaction. Specifically, reliability and responsiveness significantly impact service quality, competitor price significantly influences price, and uniqueness significantly affects brand image. The study underscores the importance of maintaining high service quality standards, competitive pricing strategies, and distinctive brand images to enhance customer satisfaction in the postal service industry. The findings offer practical implications for PT. Pos Indonesia, suggesting the prioritization of reliability and responsiveness in service delivery, competitive pricing strategies, and leveraging unique brand attributes for market differentiation. Future research directions include exploring additional variables and employing qualitative methods to deepen understanding and optimize customer satisfaction strategies. Highlight: Study: Service, price, brand influence postal customer satisfaction significantly. Regression: Reliability, responsiveness, competitor price, uniqueness impact customer satisfaction. Practical: Maintain reliability, competitive pricing, leverage uniqueness for customer satisfaction. Keywoed: Customer satisfaction, Service quality, Price, Brand image, Postal services